EU Colonial Amnesia as a Bridge: Connecting EU-African Relations and African Minorities Discrimination - Eleonora Cappa (De Europa)
This article investigates the role of the lack of historical memory of colonialism in shaping relations between the European Union (EU) and Sub-Saharan Africa. In this regard, an internal and an international perspective have been brought together, as an analysis of the impact of the lingering colonial culture on minority discrimination within the EU should also consider the development of reciprocal relations on a foreign level.